Spiral Progression Approach in Science Curriculum: Student Perception on its Implementation - Acut Junpel (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The student’s perception on the implementation of spiral progression approach in science curriculum was studied using descriptive survey method. It also seeks to identify the profile of students and to determine how the spiral progression approach in science curriculum enhances the learning process. A researcher-made questionnaire was the instrument used in the study considering the four factors, namely: teaching strategies, instructional materials, equipment and apparatus and science laboratory room. The results of the study showed that majority of the respondents were13-15 years old, females, 3-4 number of siblings, family monthly income of Php 1,001-5,000, and parent’s educational attainments were high school level.  The overall perception of the respondents on the spiral progression approach in science curriculum in terms of teaching strategies, instructional materials, equipment and apparatus, and laboratory room was rated agree. The overall mean on how can the spiral progression approach enhance the learning process was 2.93. This further mean that in enhancing the new science curriculum one should consider the teaching strategies used by teachers, the availability of instructional materials, equipment, apparatus and science laboratory room. School administrators should proactively respond to the needs of their schools concerning on the availability of science equipment, apparatus, instructional materials, and science laboratory room to enhance the effective teaching-learning process and to improve teaching effectiveness on teachers.